Reproducción del cucarachero común (troglodytes aëdon, aves, troglodytidae) en el valle del cauca (1984)
The breeding biology of the Southern House Wren was investigated at 24 nests between may 1977 and february 1979 in the Cauca Valley (3°32' 20" N, 76° 31' 57" W, 976 m), Colombia. Eleven adults and 33 juveniles were banded for individual identification. Males maintained permanent, multiple purpose territories throughout the year. Preliminary estimates of territory size ranged from 0.12 to 0.28 Ha. Pair bonds lasted several nestings in succession, and all changes in composition of the pairs followed disappearance of one of the members.Nest-boxes were readily accepted. Male and female cooperated in nest building but the latter contributed most of the material during the final stage.Building lasted between 8 and 37 days. Eggs were laid early in the morning at intervals of about 24 hr, and averaged 18.5 x 13.5 mm and 1.9 g. Clutch size ranged from 2 to 4 eggs, and averaged 3.2. One female laid 7 clutches (20 eggs) in 17 months, with a minimum interval of 48 days between clutches.Females alone incubated and devoted 65-88% of her diurnal time to this chore. Incubation period averaged 15 days, and hatching was either serial or simultaneous. For the firs seven days after hatching the female broded the young for 37% of her diurnal time. Both parents fed the young, the contribution by the female being significantly greater. Young were fed at an hourly average rate of 2.8 times per capita. Lepidoptera, grasshopers, and spiders together accounted for 80% ofthe items brought to the nestlings. After fledging the young were fed for about two weeks. Young fledged between 16 and 21 days after hatching.Their deyelopment and behavior are described, and growth curves are given for body weight and length of first primary. Some juveniles stayed in the parental territories for as long as three months after fledging, and thus coincided with second nestings by their parents during this period but did not play any role in the rearing of siblings. Productivity averaged 2.8 fledgelings per brood, a 90.2% nesting success. Breeding activity was recorded in every month of the year except March. Peaks of breeding in april and november-december coincided with rainfall peaks.